Evaluación, seguimiento y recuperación de la cartera crediticia en Mi Banco – Banco de la Microempresa sede Trujillo, periodo 2018 - 2021 - Sánchez Llerena, Jimmy Edinson (2022)
The following professional sufficiency report aims to evaluate credit management in the process of evaluation, monitoring and recovery of credits in Mibanco period 2018 - 2021; within the problems detected, Mibanco presents difficulties in the evaluation to grant credits, in the monitoring and recovery of credits, due to the fact that a deficient evaluation of the management to grant credits is recorded, since these are granted without a good file likewise, clients incur delays in the payment of their installments, due to the lack of payment capacity to face their credit debts, which generates that a credit is irrecoverable. The results indicated: The credit portfolio quality of Mibanco headquarters Trujillo in the year 2021 was 23.11%, in the year 2020 it was 31.55%, in the year 2019 it was 15.77% and in the year 2018 it was 18.99%. The delinquency rate in 2021 was 9.78%, in 2020 it was 17.67%, in 2019 it was 7.59, and in 2018 it was 9.28%. It is recommended to the Administrator of the Agency Mibanco Trujillo Office to require credit analysts to fully comply with policies and procedures, in order to reduce errors that occur in the process of evaluation, analysis and approval of credit to the microentrepreneurs.